Cryostratigraphy and ground-ice content of the upper permafrost at the Jago River study site, Northern Alaska, July-August 2018 ... - Kanevskiy, Mikhail; Jorgenson, Torre; Liljedahl, Anna; Daanen, Ronald P. (NSF Arctic Data Center, 2020)
This dataset contains information on cryostratigraphy and ground-ice content of the upper permafrost, which was based on the results of field work at the Jago River study site located approximately 45 kilometers (km) south of Kaktovik. In July-August 2018, 50 boreholes up to 5.2 meters (m) deep were drilled along the transect that had been established in August 2009. Thirteen of them were re-drilled at the same sites where ice wedges were degrading or stabilizing in 2009 and one borehole with number C43-MS1 – in the center of polygon. Entire cores were described and photographed in the field, and ground-ice contents of frozen soils (including gravimetric and volumetric moisture contents, excess-ice content) were determined. The dataset includes cryostratigraphic descriptions, ice-content values, and photographs of the frozen cores obtained from 50 boreholes. ...